The SAGE handbook of qualitative methods in health research - Bourgeault, Ivy Lynn, 1967-; Dingwall, Robert; De Vries, Raymond G. (London : SAGE, 2010)
There has been a growing interest in the health community in the use of qualitative methods to answer questions about policy or practice that cannot be addressed with the conventional quantitative approaches of most clinical or experimental research. This handbook provides a comprehensive overview specifically compiled for this market.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Health -- Research -- Methodology; Medicine -- Research -- Methodology; Qualitative research; Medical policy; Health -- Research -- Methodology -- Case studies; Medicine -- Research -- Methodology -- Case studies